Distribuição espacial da tuberculose em um município do interior do estado de São Paulo entre 2008 - 2013 - Fusco, Alcione Pereira Biffi (Universidade Federal de São Carlos, 2015)
Objective : To analyze the spatial distribution of tuberculosis cases in São Carlos / SP. Method : descriptive and ecological study of tuberculosis cases registered in the tb-web information system, between the years 2008 and 2013. Results: We identified 315 cases (addresses), and, of this total, 290 cases were geocoded, which corresponds to 92%. Most of these cases were male (n = 224; 70.89%), median age of 40 years and with the pulmonary clinical presentation predominant (n = 257; 81.33%). The distribution was not random or heterogeneous, representing specific areas of the municipality in epidemiological terms. Conclusion: The study showed that the city needs improvement with regard to aspects related to the management and planning of health services, strengthening the decentralization actions in relation to primary health care. In this sense, it is essential to increase the early detection and prevention actions, stimulating treatment adherence and active pursuit, contributing, consequently, to the improvement of tuberculosis patient’s care and their social environment.
Spatial distribution of tuberculosis in a São Paulo state city, 2008-2013
Keywords: Atenção primária à saúde; Tuberculose; Geoprocessamento; Distribuição espacial da população; Primary health care; Tuberculosis; Geoprocessingcs; Residence characteristics; CIENCIAS DA SAUDE